The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10162-013-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and Patterns of Hearing Loss

Abstract: Tinnitus is strongly linked with the presence of damaged hearing. However, it is not known why tinnitus afflicts only some, and not all, hearing-impaired listeners. One possibility is that tinnitus patients have specific inner ear damage that triggers tinnitus. In this study, differences in cochlear function inferred from psychophysical measures were measured between hearing-impaired listeners with tinnitus and hearing-impaired listeners without tinnitus. Despite having similar average hearing loss, tinnitus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 21 publications
(32 reference statements)
2
42
0
Order By: Relevance
“…Tan et al [2013] demonstrated that patients with chronic tinnitus tended to experience high-frequency hearing loss, better frequency selectivity and compression. This difference may be caused by the different mechanisms between acute and chronic tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [2013] demonstrated that patients with chronic tinnitus tended to experience high-frequency hearing loss, better frequency selectivity and compression. This difference may be caused by the different mechanisms between acute and chronic tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Within a run, the masker level was varied to determine the masking threshold for the probe. Between runs, the masker frequency was changed randomly across the following values, 0.5, 0.7, 0.9, 1, 1.1, 1.2, 1.3 and 1.6 times the probe frequency and resulted in an iso-forward masking contour (IFMC; Meddis et al, 2010;Lecluyse et al, 2013;Tan et al, 2013). IFMCs were generated for probe frequencies 0.25, 0.5, 1, 2, 4, and 6 kHz.…”
Section: General Principlesmentioning
confidence: 99%
“…The development and assessment of the measurement procedures have been described elsewhere Tan et al, 2013). Their aim is to generate an auditory profile that summarizes basic aspects of auditory functioning while also being simple enough to be used in the context of computer modelling.…”
mentioning
confidence: 99%
“…The high-threshold ANFs most vulnerable to damage by noise exposure (Furman et al, 2013) or to deterioration with aging (Sergeyenko et al, 2013) are those with high frequency tuning (Kujawa and Liberman, 2009), which is consistent with the percepts reported in audiometrically normal tinnitus (Roberts et al, 2008;Schaette and McAlpine, 2011). Cochlear factors may also explain why not all individuals with high frequency hearing loss detected by the audiogram develop tinnitus (Tan et al, 2013). High threshold ANFs with high frequency tuning could be better preserved in such individuals, although this question has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%